Don’t Be Afraid to Change: Work Environment and Workload Affects Cyberloafing Behavior - Aulia, Irfan Noviandy; Karyatun, Subur; Hidayat, Rafi Ramadhan; Soelton, Mochamad (Archives of Business Research, 2023)
Internet technology can have a positive impact on companies in helping the effectiveness and efficiency of company operations, such as faster information delivery, more up to date receiving information, reduced production time and more efficient service delivery. This study aims to analyze the work environment and workload on cyberloafing behavior and employee performance at the Tangerang I State Property and Auction Service Office. The population in this study was 30 employees. The sample used was all 30 employees, namely the saturated sample. The data collection method uses a survey method, with the research instrument being a questionnaire. The data analysis method uses Partial Least Square. The analysis used in this research is quantitative analysis using data collection methods through questionnaires. Structural equation modeling (SEM) is used as an analysis method and Smart PLS is used as an analysis tool. Findings: The work environment has a positive and significant effect on Employee performance, workload has a negative and significant effect on employee performance. The work environment and workload have a positive and significant effect on Cyberloafing. Meanwhile, cyberloafing has a negative and significant effect on employee performance.